Characterization of Porous Silicon Nanoparticles for Biomedical Applications - Kaasalainen, Martti (fi=Turun yliopisto|en=University of Turku|, 2017)
Porous silicon (PSi) is an intriguing material for biomedical applications because a great variation of properties can be created by adjusting fabrication parameters.Physicochemical properties, including pore size, surface area, surface chemistryand material dimensions, are dictating PSi behavior in biological environments.Degradation rate and drug loading capacity, as well as interactions with cellmembranes and blood proteins correlate with these properties. When materialdimensions are approaching the nanoscale, significant benefits, like efficient bio-distribution and permeation through biological membranes, can be achieved.Unfortunately, nanoscale objects are challenging to characterize because thephysical models that explain regularities in the nanoscale world are significantlydifferent compared with the macroscopic world. Thus, careful basic studies andlinking material properties to its performance is important when designing functional materials for biomedical applications. In this thesis, nanoparticle characterization with light scattering techniques and nanoparticle properties in biologically and pharmacologically relevant conditions are studied. During the research, we have found electrophoretic light scattering (ELS) and zeta potential to be a convenient way to characterize PSi nanoparticles’ surface chemistry and colloidal stability. Multiangle light scatterings (dynamic and static light scattering) proved to be useful phenomena when structure, agglomeration, and size of mesoporous nanoparticles needed to be revealed in their natural colloidal form. ELS studies did also show that isotonic media and peptide adsorption play a pivotal role in the stability and zeta potential of PSi nanoparticles. These results highlight the importance of medium dependent characterization of nanoparticles and show the versatility of light scattering experiments for this purpose. The role of medium in loading peptides into PSi nanoparticles has also been studied, and pH was found to have a significant effect. Despite the general assumption, the highest loading degree was achieved in pH conditions where the total charge of the peptide was close to zero. Peptide adsorption at low loading concentrations was found to be very strong, especially on hydrophobic particles, and part of the peptide payload was irreversibly adsorbed. In in vivo studies, the loading of peptides into PSi nanoparticles sustained the peptide release in subcutaneous delivery from 26 min to more than 20 hours. Intravenously administered nanoparticles did not cause notable sustained release. These results are indicating that loading conditions may affect the release of peptides from PSi nanoparticles. The possibility to tune the peptide release by altering loading conditions makes PSi nanoparticles an interesting candidate forthe sustained subcutaneous delivery of peptide drugs.